Knockdown of Mns1 Increases Susceptibility to Craniofacial Defects Following Gastrulation‐Stage Alcohol Exposure in Mice. (10th September 2018) - Boschen, Karen E.; Gong, Henry; Murdaugh, Laura B.; Parnell, Scott E.
Abstract : Background: MNS1 (meiosis‐specific nuclear structural protein 1) is necessary for motile cilia function, such as sperm flagella or those found in the embryonic primitive node. While little is known regarding the function or expression pattern of MNS1 in the embryo, co‐immunoprecipitation experiments in sperm have determined that MNS1 interacts with ciliary proteins, which are also important during development. Establishment of morphogenic gradients is dependent on normal ciliary motion in the primitive node beginning during gastrulation (gestational day [GD] 7 in the mouse, second–third week of pregnancy in humans), a critical window for face, eye, and brain development and particularly susceptible to perturbations of developmental signals. The current study investigates the role of Mns1 in craniofacial defects associated with gastrulation‐stage alcohol exposure. Methods: On GD7, pregnant Mns1 +/− dams were administered 2 doses of ethanol (5.8 g/kg total) or vehicle 4 hours apart to target gastrulation. On GD17, fetuses were examined for ocular defects by scoring each eye on a scale from 1 to 7 (1 = normal, 2 to 7 = defects escalating in severity). Craniofacial and brain abnormalities were also assessed. Results: Prenatal alcohol exposure (PAE) significantly increased the rate of defects in wild‐type fetuses, as PAE fetuses had an incidence rate of 41.18% compared to a 10% incidence rate in controls. Furthermore, PAE interacted with genotype to significantly increase the defect rate and severity in Mns1 +/− (64.29%) and Mns1 − /− mice (92.31%). PAE Mns1 − /− fetuses with severe eye defects also presented with craniofacial dysmorphologies characteristic of fetal alcohol syndrome and midline tissue loss in the brain, palate, and nasal septum. Conclusions: These data demonstrate that a partial or complete knockdown of Mns1 interacts with PAE to increase the susceptibility to ocular defects and correlating craniofacial and brain anomalies, likely though interaction of alcohol with motile cilia function. These results further our understanding of genetic risk factors that may underlie susceptibility to teratogenic exposures. Abstract : Prenatal alcohol exposure can result in birth defects involving the brain and face; these effects can be modified by environmental and genetic factors. Here, we investigate the influence of the cilia gene Mns1 on susceptibility to birth defects in a mouse model of FASD. Partial or complete loss of Mns1 increases the incidence and severity of eye, craniofacial, and brain malformations following early gestational alcohol exposure, demonstrating that prenatal alcohol interacts with cilia and identifies a genetic risk factor that increases sensitivity to alcohol.